Uso da corrente crítica por meio da simulação para o auxílio no processo de planejamento da capacidade em uma fundição - Santos, Fabrício Guermandi dos (Universidade Federal de São Carlos, 2013)
It is already known that the productive environment is in constant changing, with new technologies, new systems and theories coming up every day, providing other forms to manage production to comply with inconstant demands and a competitive market. In this context, the capacity planning has an important role for a company, managing resources in a structured way with accurate information, ensuring that market requirements will be fulfilled in terms of delivery, cost and quality. The Critical Chain Method is shown as an alternative to change the way that manufacturing resources has been managed, prioritizing what is really important, avoiding waste of time and financial resources. Therefore, the objective of this work was to elaborate a model of discrete-event simulation to evaluate and compare the use of the principles of critical chain, against the traditional capacity planning method used in a foundry. For this assessment were used performance indicators as accomplishment deadlines, work in process, average lead time, etc., where these after being compared, have shown the proposed method could provide positive results to the environment studied.
Keywords: Planejamento da produção; Planejamento da capacidade; Fundição; Corrente crítica; Simulação; Capacity Planning; Foundry; Critical chain; Simulation; ENGENHARIAS::ENGENHARIA DE PRODUCAO